Предмет: Алгебра, автор: Reideen

Упростите выражение
( \frac{ \sqrt{m} - 2}{ \sqrt{m} + 2}  +  \frac{8 \sqrt{m}}{m - 4}) \div  \frac{ \sqrt{m}  + 2}{m - 2 \sqrt{m} }

Ответы

Автор ответа: Universalka
1

1)\frac{\sqrt{m}-2 }{\sqrt{m}+2 }+\frac{8\sqrt{m} }{m-4}=\frac{\sqrt{m}-2 }{\sqrt{m}+2 }+\frac{8\sqrt{m} }{(\sqrt{m} +2)(\sqrt{m}-2)}}=\frac{(\sqrt{m}-2)^{2}+8\sqrt{m}}{(\sqrt{m}+2)(\sqrt{m}-2)}=\frac{m-4\sqrt{m}+4+8\sqrt{m}}{(\sqrt{m}+2)(\sqrt{m}-2)}=\frac{m+4\sqrt{m} +4}{(\sqrt{m}+2)(\sqrt{m}-2)} =\frac{(\sqrt{m}+2)^{2}}{(\sqrt{m}+2)(\sqrt{m}-2)}=\frac{\sqrt{m}+2}{\sqrt{m}-2 }

2)\frac{\sqrt{m}+2 }{\sqrt{m}-2}:\frac{\sqrt{m} +2}{m-2\sqrt{m} }=\frac{\sqrt{m}+2 }{\sqrt{m}-2 }*\frac{\sqrt{m}(\sqrt{m}-2)}{\sqrt{m}+2}=\sqrt{m}

Похожие вопросы